2004
DOI: 10.1111/j.1365-2249.2004.02454.x
|View full text |Cite
|
Sign up to set email alerts
|

Transfer factors as immunotherapy and supplement of chemotherapy in experimental pulmonary tuberculosis

Abstract: SUMMARYProblems of logistics, compliance and drug resistance point to an urgent need for immunotherapeutic strategies capable of shortening the current six month antibiotic regimens used to treat tuberculosis. One potential immunotherapeutic agent is transfer factors. Transfer factors (TF) are low molecular weight dialysable products from immune cells which transmit the ability to express delayed-type hypersensitivity (DTH) and cell mediated immunity from sensitized donors to nonimmune recipients. In this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
35
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 29 publications
6
35
0
Order By: Relevance
“…The peak of immune protection in this animal model reached in day 21. This agree with a study done by Fabre [10] in Mexico, used Transfer Factor as immunotherapy and supplement of chemotherapy in experimental pulmonary tuberculosis [10]. The current study found that the effect of administration of murine transfer factor (TF) on survival of challenged mice was majority (83.3%) comparing with maximum (100%) mortality of the control group, and this result obtained is in accordance with a study done in Mexico 2004 by Fabre (Transfer factors as immunotherapy and supplement of chemotherapy in experimental pulmonary tuberculosis)where they found that the BALB/c mice which were infected via the trachea with Mycobacterium tuberculosis H37Rv and treated with mTF showed a significant 95% survival when compared with the control group, which exhibited 100% mortality.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The peak of immune protection in this animal model reached in day 21. This agree with a study done by Fabre [10] in Mexico, used Transfer Factor as immunotherapy and supplement of chemotherapy in experimental pulmonary tuberculosis [10]. The current study found that the effect of administration of murine transfer factor (TF) on survival of challenged mice was majority (83.3%) comparing with maximum (100%) mortality of the control group, and this result obtained is in accordance with a study done in Mexico 2004 by Fabre (Transfer factors as immunotherapy and supplement of chemotherapy in experimental pulmonary tuberculosis)where they found that the BALB/c mice which were infected via the trachea with Mycobacterium tuberculosis H37Rv and treated with mTF showed a significant 95% survival when compared with the control group, which exhibited 100% mortality.…”
Section: Discussionsupporting
confidence: 94%
“…Mexican team of investigators have shown that treatment of mice infected with M. tuberculosis with a murine tuberculosis-specific TF restored expression of the Th1 cytokine pattern and resulted in inhibition of bacterial proliferation, significant increase of DTH, and animal survival [10]. The efficiency of TF was highly depended on the dose and, to its source (murine, human or bovine),colostrums is rich in transfer factor.4lifeTransfer Factor, American company is famous and well known in the production of TF.…”
Section: Discussionmentioning
confidence: 99%
“…The specific TF was produced from tuberculous BALB/c mice following intra-tracheal infection. The treatment with TF leads to restoration of the expression of the Th1 cytokine pattern, whereas the increase of delayed type hypersensitivity leads to inhibition of bacterial proliferation and animal survival [62].…”
Section: Mycobacterial Infectionmentioning
confidence: 99%
“…They are related to restoration of the expression of the Th1 cytokine pattern, increase in DTH, leading to inhibition of bacterial proliferation and better animal survival. [60] TF preparations have also been tested against M. leprae, M. fortuitum pneumonia and M. xenori (as mentioned in [27]). …”
Section: Mycobacterial Infectionmentioning
confidence: 99%